STUDI KASUS PEMBERIAN MASSAGE PUNGGUNG DENGAN MINYAK AROMATERAPI LAVENDER UNTUK MENGATASI GANGGUAN POLA TIDUR - Silvia Septiani Lumban Gaol; Regina Natalia (CV. Adiba Aisha Amira, 2025)
Humans experience several health disorders, including sleep pattern disorders, where clients complain of difficulty sleeping at night, frequently wake up during the night and are unable to fall back asleep, and appear weak. Therefore, the primary nursing diagnosis is a sleep pattern disorder. One method used is to apply a back massage with lavender aromatherapy oil. The purpose of this writing is to find out nursing care on patient with rest and sleep needs for giving back massage with lavender aromatherapy oil to overcome sleep pattern disorders. The method used is a case study conducted based on the stages of nursing care including assessment, diagnosis, intervention, implementation and nursing evaluation. The results of the study showed data found her in the form of clients looking weak, appearing dark circles around the eye area. With the nursing problem is disturbed sleep patterns, so researchers arrange sleep support interventions with actions taken in the form of giving back massage with lavender aromatherapy oil show the results of the problem is resolved. Suggestions for health services and families are to provide back massage with lavender aromatherapy oil to overcome the problem of disturbed sleep patterns.